Influence of fuel subsidy removal on the prices of major food commodities in southeastern Nigeria (West African Journal on Sustainable Development, 2024)
Recently there has been an astronomical increase in food prices with resultant indication in food insecurity. This is positively correlated with the total removal of fuel subsidy. Therefore, this study examined the influence of subsidy removal on prices of food items in Southeastern Nigeria. Data for this study was obtained from National Bureau of Statistics. Data was analysed using descriptive and inferential statistics (t- test) and presented in histogram and bar charts.  The result showed that the prices of Rice, Beans, Yam, Garri and Tomato were significantly different after the subsidy removal at 10% level of significance and only Palm Oil was significant at 5% level of significance. There is a speedy rise in food price and other commodities within this short period of subsidy removal. This has resulted to different categories of hardships to the populace, affecting the economy of the country and leading to an unprecedented rise in exchange rate.The consequences continued to affect importation of valued materials into the country. Agricultural production is affected due to high cost of farming inputs and food security is compromised. Therefore, improvement in the transportation system, provision of palliative measures and reduction of corruption will in no small measure increase food production, food security and sustainable livelihood.
Keywords: Fuel subsidy removal; food price; food security; livelihood